Pelaksanaan Hukuman Mati dalam Perspektif Hak Asasi Manusia - Nebi, Oktir; Saputra, Warfian (Universitas Batanghari Jambi, 2026)
The death penalty is a sanction imposed by taking the life of a person who has violated the law. In Indonesia, there is a debate regarding the death penalty when viewed from a Human Rights perspective. Opinions supporting the death penalty argue that such action does not violate Human Rights because the perpetrator has harmed the Human Rights of the victim and society. On the other hand, there are also views that reject the death penalty on the grounds that taking someone's right to life, which should be highly respected, should not be carried out by anyone. Therefore, there is pressure for the death penalty to be abolished in the applicable regulations. The questions to be discussed in this study include How is the Implementation of the Death Penalty in Indonesia and What is the Human Rights perspective on the implementation of the death penalty in Indonesia? This paper attempts to provide insight into the death penalty from a Human Rights perspective in Indonesia, both from the perspective of applicable legal theory and from current practice. This research is a normativelegal research conducted through a literature review by analyzing various primary, secondary, and tertiary legal sources. In addition, researchers also conducted observations on the practice of the death penalty, public responses regarding the implementation of the law, and conducted interviews if necessary with practitioners or experts in the fields of law, sociology, and politics.